Geometric decomposition and analysis of Konya Sahip Ata mosque portal muqarnas - Sevde Gülizar Dincer (Heritage Science)
Abstract In the late Anatolian Seljuk period (1243–1308), architectural design took on new symbolic significance, focusing on grandeur and ornamentation as a response to the shifting political landscape. One of the critical features of this era is the transformation seen in the geometric layouts of some muqarnas designs, exemplified explicitly in Konya Sahip Ata mosque muqarnas (1258). While the arrangements may appear irregular at first glance, closer analysis reveals that they are structured according to a dodecagonal system. This study focuses on the geometric layouts in the plan projections of Sahip Ata mosque muqarnas, showing that dodecagrams were used to organize these complex patterns, reflecting an advanced and deliberate approach to design during this transitional period.